Pers, demokrasi dan negara Indonesia Post-Soeharto: Sebuah perspektif - Herdi Sahrasad (Masyarakat, Kebudayaan dan Politik, 2014)
The resignation of President Soeharto in May 1998 marked the end of new order era and started a fundamental change within democracy in Indonesia. As a democratic state, Indonesia arguably provides a system to guarantee the freedom of press and good environment of mass media; as the media is supposedly not to be power driven. Several factors have been observed to understand the relationship between press and democracy. Those are democratic revolution, freedom of press, political oligarchy, the role of students, and criminal democracy practice in Indonesia. This article found that under  the President Susilo Bambang Yudhoyono-Boediono (SBY-Boediono) era, newspeople freedom in journalism was gripped by the practice of "criminal democracy" which continues to undermine the development of press freedom. To conclude, democracy in Indonesia is decayed by unjust practices from the political elites; it further affects the way press and mass media in performing their roles as the fourth pillar of democracy.